The Institutional Drivers of Economic Growth in the MENA Region: A Multidimensional Analysis of Direct and Mediated Effects - Farjallah, Nadia (Journal of Posthumanism, 2025)
The aim of this article is to study the impact of institutional quality on economic growth in the MENA region in particular, and to identify certain institutional shortcomings. We proceeded by estimating GMM in a system on cross-sectional data for a sample of 18 countries over the period 1984-2023. The results show that political stability has a positive direct effect, as well as a positive indirect effect through the positive accumulation of human and physical capital, and a negative effect through income inequality. Corruption thus has a negative impact on economic growth, on the one hand through a reduction in human and physical capital, trade openness and political stability, and on the other through an increase in inflation and public spending. Democracy has a negative impact on economic growth through increased human capital, political stability and trade openness, while income inequality, government spending and physical capital contribute to its reduction.